Factor Structure of PTSD Symptoms in Opioid-Dependent Patients Rating Their Overall Trauma History - Reddy, Madhavi K. (2013)
BACKGROUND: The current standard for posttraumatic stress disorder (PTSD) diagnosis is a 3-factor model (re-experiencing, avoidance, and hyperarousal). Two 4-factor models of PTSD, the emotional numbing model (re-experiencing, avoidance, emotional numbing, and hyperarousal) and the dysphoria model (re-experiencing, avoidance, dysphoria, and hyperarousal), have considerable empirical support in the extant literature. However, a newer 5-factor model of PTSD has been introduced that is receiving interest. The 5-factor model differs from the four-factor models in its placement of three symptoms (irritability, sleep disturbance, and concentration difficulties) into a separate cluster termed dysphoric arousal. We empirically compared the theoretical factor structures of 3-, 4-, and 5-factor models of PTSD symptoms to find the best fitting model in a sample of opioid dependent hospitalized patients. METHODS: Confirmatory factor analyses were conducted on the 17 self-reported PTSD symptoms of the Posttraumatic Checklist- Civilian Version (PCL-C) in a sample of 151 men and women with opioid dependence. RESULTS: Both four-factor models fit the observed data better than the three-factor model of PTSD; the dysphoria model was preferred to the emotional numbing model in this sample. The recently introduced five-factor model fit the observed data better than either four factor model. CONCLUSIONS: PTSD is a heterogeneous disorder comprised of symptoms of re-experiencing, avoidance, numbing, and dysphoria. Three symptoms, irritability, sleep disturbance, and concentration difficulties, may represent a unique latent construct separate from these four symptom clusters in opioid dependent populations who have experienced traumatic events.